PENGARUH PENGETAHUAN TENTANG BENCANA BANJIR TERHADAP KESIAPSIAGAAN REMAJA DALAM MENGHADAPI BENCANA BANJIR DI KELURAHAN PETAMBURAN, KECAMATAN TANAH ABANG, JAKARTA PUSAT - Sri Nurviana Mellenia; Muzani Jalaludin; Fauzi Ramadhoan A’rachman (JURNAL GEOGRAFI, 2022)
This study aims to determine the effect of knowledge about flood disasters on adolescent preparedness in dealing with floods in Petamburan Village, Tanah Abang District, Central Jakarta. The population in this study are teenagers who live in Petamburan Village, Central Jakarta, while the sample used is 99 respondents using purposive sampling technique. The criteria used as samples in this study were teenagers who had experienced a flood disaster. The data analysis technique in this research is descriptive percentage and simple linear regression. Simple linear regression analysis to identify the influence of knowledge on youth preparedness in facing flood disaster. The results showed that the knowledge of adolescents about flood disasters was included in the very high criteria with an average of 83.43%. When viewed from the parameters of age, education, and length of stay, it can be seen that the higher the age, education, and length of stay, the higher the level of knowledge. When viewed from the gender parameter, it does not show a significant change to the level of knowledge. Adolescent preparedness in facing flood disaster has an index value of 81.45 which is included in the category of high preparedness. When viewed from the parameters of age, education, and length of stay, it can be seen that the higher the age, education, and length of stay, the higher the level of preparedness. When viewed from the gender parameter, it did not show a significant change in the level of preparedness. Based on the results of simple linear regression data analysis obtained a significance value (Sig) of 0.000. With a significance value of 0.000 < 0.050, Ha is accepted and H0 is rejected, so there is a significant influence between knowledge about flood disasters and adolescent preparedness in dealing with flood disasters in Petamburan Village. The value of the coefficient of determination of 0.626 means that changes in adolescent preparedness in dealing with floods in Petamburan Village of 62.6% are influenced by knowledge about disasters. Keywords: Knowledge about flood disaster, Preparedness, Flood Disaster